Preacher woman sings the blues : the autobiographies of nineteenth-century African American evangelists - Douglass-Chin, Richard J. (University of Missouri Press, 2001)
"Preacher Woman Sings the Blues begins with the study of black evangelists Belinda, Jarena Lee, and Zilpha Elaw, continuing with Rebecca Cox Jackson, Sojourner Truth, Julia Foote, Amanda Smith, Elizabeth, and Virginia Broughton. The author's discussion of Zora Neale Hurston focuses on how Hurston operates as a connection between early black women evangelist writers and black women writing in America today. He ends with the works of Alice Walker, Toni Morrison, and Toni Cade Bambara." "By examining the early traditions prefiguring contemporary African American women's text and the impact that race and gender have on them, Douglas-Chin shows how the nineteenth-century black women's works are still of utmost importance to many African American writers today. Preacher Woman Sings the Blues makes a valuable contribution to literary criticism and theoretical analysis and will be welcomed by scholars and students alike."--Jacket